2020
DOI: 10.3390/brainsci10020080
|View full text |Cite
|
Sign up to set email alerts
|

Balance Training with Electromyogram-Triggered Functional Electrical Stimulation in the Rehabilitation of Stroke Patients

Abstract: This study was conducted to investigate the effects of balance training with electromyogram-triggered functional electrical stimulation (EMG-triggered FES) to improve static balance, dynamic balance, and ankle muscle activation in stroke patients. Forty-nine participants (>6 months after stroke) were randomly assigned to the experimental group (n = 25) and the control group (n = 24). The experimental group underwent balance training with EMG-triggered FES for 40 min a day, 5 days a week, for a 6-week period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“… 37 ) As balance ability is an important goal of stroke rehabilitation, a recent study reported that the combination of balance training with FES was is acceptable and effective in improving static and dynamic balance. 38 ) In a long-term follow-up randomized controlled trial over 12 months, FES showed similar effects to ankle-foot orthosis in all primary outcomes related to gait quality and function, suggesting that FES may be an appropriate alternative to orthosis for individuals with chronic stroke. 39 )…”
Section: Functional Electrical Stimulationmentioning
confidence: 85%
“… 37 ) As balance ability is an important goal of stroke rehabilitation, a recent study reported that the combination of balance training with FES was is acceptable and effective in improving static and dynamic balance. 38 ) In a long-term follow-up randomized controlled trial over 12 months, FES showed similar effects to ankle-foot orthosis in all primary outcomes related to gait quality and function, suggesting that FES may be an appropriate alternative to orthosis for individuals with chronic stroke. 39 )…”
Section: Functional Electrical Stimulationmentioning
confidence: 85%
“…This is a critical theory that directly relates to improving muscle activity abnormalities that occur during walking in patients with stroke to improve walking. The effect of balance learning on gait improvement by electrical stimulation for patients with stroke as an approach to muscle response was recently reported [16]. This suggests that adjusting the response of muscle activity to posture changes can positively affect muscle exertion during walking, leading to improved walking.…”
Section: Introductionmentioning
confidence: 91%
“…-The Review study indicated that physical activity serve as a prototypic preconditioning stimulus that provides protection to the brain in patients with acute or chronic strokes. 41,42 -Exercise significantly improves the emotional and physical health of patients with Alzheimer's disease. 43 -Patients with neurodegenerative conditions indicated that physical activity can improve posture, balance, tremor, mobility, handgrip as well as motor coordination in patients with Parkinson's disease.…”
Section: Benefits Of Physical Activity In Neurological Conditionmentioning
confidence: 99%